Human brain pathology in myotonic dystrophy type 1: A systematic review. Issue 1 (17th February 2021) - Weijs, Ralf; Okkersen, Kees; van Engelen, Baziel; Küsters, Benno; Lammens, Martin; Aronica, Eleonora; Raaphorst, Joost; van Cappellen van Walsum, Anne‐Marie
Abstract : Brain involvement in myotonic dystrophy type 1 (DM1) is characterized by heterogeneous cognitive, behavioral, and affective symptoms and imaging alterations indicative of widespread grey and white matter involvement. The aim of the present study was to systematically review the literature on brain pathology in DM1. We conducted a structured search in EMBASE (index period 1974–2017) and MEDLINE (index period 1887–2017) on December 11, 2017, using free text and index search terms related to myotonic dystrophy type 1 and brain structures or regions. Eligible studies were full‐text studies reporting on microscopic brain pathology of DM1 patients without potentially interfering comorbidity. We discussed the findings based on the anatomical region and the nature of the anomaly. Neuropathological findings in DM1 can be classified as follows: (1) protein and nucleotide deposits; (2) changes in neurons and glial cells; and (3) white matter alterations. Most findings are unspecific to DM1 and may occur with physiological aging, albeit to a lesser degree. There are similarities and contrasts with Alzheimer's disease; both show the appearance of neurofibrillary tangles in the limbic system without plaque occurrence. Likewise, there is myelin loss and gliosis, and there are dilated perivascular spaces in the white matter resemblant of cerebral small vessel disease. However, we did not find evidence of lacunar infarction or microbleeding. The various neuropathological findings in DM1 are reflective of the heterogeneous clinical and neuroimaging features of the disease. The strength of conclusions from this study's findings is bounded by limited numbers of participants in studies, methodological constraints, and lack of assessed associations between histopathology and clinical or neuroimaging findings.